The effect of chitin flakes on the luminous bacterium CLM3 and its biochemical characterization. - Salinas, Susan May C.
The incorporation of chitin flakes into the seawater greatly increase the microbial growth of all the microorganisms present but the addition of chitin flakes in the seawater cannot sustain the entire nutritional requirement for microbial growth of most of the bacteria. The CLM3 luminous bacterium has the greatest microbial growth in the bacterial populations suggesting that they chitinolytic bacteria., The CLM3 luminous bacterium, through morphological and biochemcial tests, was presumptively identified as Vibrio harveyi. Since Vibrio harveyi is an important pathogen in crustaceans, further confirmatory identification and pathogenic testing are recommended.